(untitled) (International Journal of Health, Animal Science and Food Safety, 2019)
In a bid to improve the productive potentials of local turkeys in developing countries, a total of 240 unsexed day-old poults arranged in a 2 × 2 factorial layout into 4 treatments with two rearing systems (indoor and outdoor) and two plumage colours (white and black) were used for this study. Poults were brooded for 4 weeks followed by an acclimatization period of 2 weeks in the two different rearing systems before the commencement of the study which lasted 10 weeks. Each treatment consisting of 60 birds was further sub-divided into six replicates of 10 birds per replicate. Data obtained were subjected to Analysis of Variance in a Completely Randomized Design. Results on performance in the grower phase showed turkeys reared in indoor system recorded significantly (p<0.05) higher weight gain (29.39 vs. 105.19 g/bird/day) and daily feed intake (27.18 vs. 98.11 g/bird/day) compare to turkeys under outdoor system. In addition, weight gain was significantly (p<0.05) higher (29.16 g/bird/day) in turkeys with black plumage than (27.42 g/bird/day) recorded in turkeys with white plumage. However, in the finisher phase turkeys under outdoor system recorded significantly (p<0.05) higher weight gain than turkeys under indoor system. In the finisher phase, interaction effects showed best weight gain and Feed Conversion Ratio (FCR) (39.22 g/bird/day and 4.60) in white-plumaged turkeys reared in outdoor system. Turkeys under outdoor system also had significantly (p<0.05) higher back and spleen percentages. However, proportions of thigh were significantly (p<0.05) higher in turkeys reared indoor. In addition, white-plumaged turkeys recorded significantly (p<0.05) higher (21.07%) cooking loss than 14.58% recorded in turkeys with black plumage. In conclusion, improved weight gain with best FCR at finisher phase as well as highest spleen portion and cooking loss in thigh meat was obtained in white-plumaged turkeys reared in outdoor system.